Events of red tides: Preventive strategies of management in Ecuador - Torres Ch, Gladys (Revista Universidad de Guayaquil, 2013)
A retrospective analysis of the existing information was made on red tides, happened in understood the coastal and insular marine area of Ecuador between 1968 and 2009, in order to locate aerial geographic of main impact, times of the occurrence, species producing causes of these events and the registries of mortality of organisms. The results demonstrated 131 events of red tide in which 26 events of mortality of organisms were included. The years of greater occurrence were in 1985 (Estero Salado), 2001 (coastal central area) and 2003 (Puná island and coasts of El Oro), possibly in answer to local oceanographic con[1]ditions. The months of main occurrence were in March, April, and May, although these also were demons[1]trated in every month of the year, coincident with the main solar radiation. The aerial geographic of the most occurrence was located in the Gulf of Guayaquil (80%), mainly in the internal channels, near of Puná island and in front of the El Oro Province, sites that are related to areas of greatest anthropogenic use. Thirty and seven species were identified cause of red tides, being the Dinophyceae class with twenty-eight species of dinoflagellates, followed by Cyanophyceae, Bacillariophyceae (three species), Raphidophyceae (two species) and one Ciliate. The Gulf of Guayaquil it was the site that had of most number of species. Me[1]sodinium rubrum was the dominant taxon with highest number of red tides, followed by Gymnodinium sp., Noctiluca scintillans and Cochlodinium catenatum. The twenty-six events were related to mortality of orga[1]nisms (fish, shrimp and larvae of shrimp) and these happened in the Gulf mainly; this not had a scientific explication, because any environmental authority at the present as it was the cause. These results establish the necessity of actions anticipated by means of a strategies proposal in the integrated management of the prevention, control and monitoring to future events of red tides and their impacts.